PROBLEMS OF LINGUISTIC GLOBALIZATION AND LANGUAGE DIVERSITY - Donoxon Abdullayeva; Lobar Nomozova (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article explores the problems of linguistic globalization and language diversity, focusing particularly on the situation in Uzbekistan. It examines how the expansion of global communication has strengthened the dominance of major languages, especially English, while posing serious challenges to the preservation of local and minority languages. The study discusses key issues such as language mixing, the increasing importance of multilingualism, and the impact of media and digital technologies on language change. Special attention is given to state language policies under Shavkat Mirziyoyev, which aim to promote foreign language learning alongside safeguarding the Uzbek language. The article also highlights the risks associated with language loss, emphasizing its deep connection to cultural identity, traditions, and national heritage. In conclusion, it stresses the need to maintain a balance between global communication and the preservation of linguistic diversity through effective educational strategies, supportive policies, and active societal engagement in protecting native languages.